High-throughput targeted screening in triple-negative breast cancer cells identifies Wnt-inhibiting activities in Pacific brittle stars - Blagodatski, Artem (Sci Rep, 2017)
Pro-proliferative oncogenic signaling is one of the hallmarks of cancer. Specific targeting of such signaling pathways is one of the main approaches to modern anti-cancer drug discovery, as opposed to more traditional search for general cytotoxic agents. Natural products, especially from marine sources, represent a largely untapped source of chemical diversity, which so far have mostly been screened for cytotoxicity. Here we present a pioneering pipeline of high-throughput screening of marine-based activities targeted against the Wnt signaling pathway, which is one of the key factors in oncogenic transformation, growth and metastasis in different cancers, including the devastating triple-negative breast cancer (TNBC) currently lacking any targeted therapies. This pipeline consisted of collection and characterization of numerous invertebrates during the SokhoBio expedition to the Kuril Basin in North Pacific, preparation of extracts from these specimen, and their screening in dedicated assays monitoring Wnt signaling in TNBC cells. This approach yielded a number of promising hits, including highly specific anti-Wnt activities targeting multiple levels within the Wnt pathway from Ophiura irrorata and other Pacific brittle stars.